1989
DOI: 10.1152/jappl.1989.66.3.1383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise of varying duration on sarcoplasmic reticulum function

Abstract: Sarcoplasmic reticulum (SR) Ca2+ uptake and Ca2+-Mg2+-ATPase activity were examined in muscle homogenates and the purified SR fraction of the superficial and deep fibers of the gastrocnemius and vastus muscles of the rat after treadmill runs of 20 or 45 min or to exhaustion (avg time to exhaustion 140 min). Vesicle intactness and cross-contamination of isolated SR were estimated using a calcium ionophore and mitochondrial and sarcolemmal marker enzymes, respectively. Present findings confirm previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
2
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 18 publications
12
86
2
2
Order By: Relevance
“…Luminal Ca 2ϩ content is dependent on several factors including, but not limited to, function of the SR Ca 2ϩ ATPase, leakiness of the SR membrane and/or RYR channel, and the total amount of Ca 2ϩ released that is a function of duration and frequency of the contractile protocol. Inhibition of the SR ATPase (22,91) and reductions in Ca 2ϩ accumulation by SR have been demonstrated after exhaustive running in rats (22,78), in single-fiber experiments (135,141), and in exercising humans (17). Evidence suggests that with prolonged stimulation resting intracellular Ca 2ϩ concentrations are significantly elevated (89).…”
Section: Sr Ca 2ϩ Release From An Experimental Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Luminal Ca 2ϩ content is dependent on several factors including, but not limited to, function of the SR Ca 2ϩ ATPase, leakiness of the SR membrane and/or RYR channel, and the total amount of Ca 2ϩ released that is a function of duration and frequency of the contractile protocol. Inhibition of the SR ATPase (22,91) and reductions in Ca 2ϩ accumulation by SR have been demonstrated after exhaustive running in rats (22,78), in single-fiber experiments (135,141), and in exercising humans (17). Evidence suggests that with prolonged stimulation resting intracellular Ca 2ϩ concentrations are significantly elevated (89).…”
Section: Sr Ca 2ϩ Release From An Experimental Perspectivementioning
confidence: 99%
“…It is possible that SR Ca 2ϩ content becomes diminished, considering that the catalytic activity of the SR Ca 2ϩ -ATPase is inhibited by a single bout of muscle activity (22,78,135) or that ''releasable'' Ca 2ϩ may be buffered by luminal phosphate that becomes elevated in skeletal muscle undergoing activity (55,103,132). This area will be addressed in BIOPHYSICAL REGULATION OF SR Ca 2ϩ RELEASE.…”
mentioning
confidence: 99%
“…A23187), and once without an ionophore in the measuring medium. The ratio of these two activities is a measure for the integrity of the membrane (BYRD et al, 1989 …”
Section: Investigations Of Muscle Camentioning
confidence: 99%
“…It has been previously suggested that glycogen may be required for contractile processes independent of energy metabolism (21). Studies in both animals (6,8,36) and humans (4) have suggested a link between sarcoplasmic reticulum Ca 2ϩ uptake and release and glycogen availability. In addition, topographical localization of glycogen within human skeletal muscle has been observed (19).…”
Section: Muscle Metabolism During Exercisementioning
confidence: 99%